MACROECONOMIC STRESS TESTING PADA PROBABILITY OF DEFAULT PERBANKAN DI INDONESIA - Ramadhani, Novilia; Maski, Ghozali (Contemporary Studies in Economic, Finance and Banking, 2022)
The objective of this research is to identify and analyze the magnitude of probability of default in Indonesian banks in the period of 2007-2021 using macroeconomic stress testing based on the severely adverse scenario simulation coming from macroeconomic variable shocks. This quantitative deductive research use multiple linear regression. The independent variables are real GDP growth, inflation, interest rate, and world oil price, while the dependent variable is probability of default that is proxied by net NPL. The stress test used in this study includes sensitivity testing amd hypothetical scenario testing. Using Bank BRI, Bank Mandiri, and Bank BCA as the sample, this research produces different effects and magnitudes in the probability of default of BUKU IV banks, in which the said probability in the overall shows sensitive results in the event of macroeconomics variable shocks. In addition, the results of the study show that the real GDP variable and world oil prices have a negative and significant effect on the probability of default of Bank BRI, Bank Mandiri, and Bank BCA, then the exchange rate variable has a positive and significant effect on the probability of default of Bank BRI, Bank Mandiri. , and Bank BCA. While the inflation variable has a positive and insignificant effect on the probability of default of Bank BRI, Bank Mandiri, and Bank BCA. The last variable, namely interest rates, has a positive and insignificant effect on Bank BRI and Bank BCA, but has a significant effect on Bank Mandiri.